Rhino-Orbito-Cerebral Mucormycosis (ROCM): An Observational Case Report of Covid-19 Positive Patients Admitted in Intensive Care Unit of Community Hospital in South India - Chimezie Finian Nwadinigwe; Mateus Sakundarno Adi; Budi Laksono; Dwi Sutiningsih (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: Rhino-orbito-cerebral mucormycosis (ROCM) increasing incidence in the setting of COVID-19 in India and elsewhere has become a matter of immediate concern. In this observational case report we have observed the signs and symptoms of ROCM among coronavirus positive patients with reference to “Mucor code “as reported by Honavar SG 2021, we have reported cases been admitted to ICU for <2weeks in a community hospital in South India. Method: Patient informed consent was taken, Patient’s data (Medical record, medication charts, daily report) were collected using a designed data collection form, observed warning signs and symptoms, and predisposed factors was noted and ROCM is characterized with reference to the “Mucor code”.Results: Nasal stuffiness, Foul smell and Facial pain and among others were the most coherent warning signs and symptoms observed among the patients in <2weeks of admission in ICU. Other observed predisposing risk factors were regular administration of corticosteroids, antibiotics, Diabetes Mellitus, Hypertension, and Kidney Stone.Conclusion: All the cases on preliminary examination on the basis of observed warning signs and symptoms were “Possible” ROCM a sub-type of Covid-19 associated mucormycosis (CAM), as this was the first reported case of the hospital. Our study gave basis for further diagnosis and monitoring of Covid-19 positive patient admitted in the intensive care units.